Corrosion Resistance of CoCrFeNiMn High Entropy Alloy Coating Prepared through Plasma Transfer Arc Claddings - Pei-Hu Gao (MDPI AG, 2021)
High entropy alloy attracts great attention for its high thermal stability and corrosion resistance. A CoCrFeNiMn high-entropy alloy coating was deposited on grey cast iron through plasma transfer arc cladding. It formed fine acicular martensite near the grey cast iron, with columnar grains perpendicular to the interface between the grey cast iron substrate and the cladding layer as well as dendrite in the middle part of the coatings. Simple FCC solid solutions present in the coatings which were similar to the powder’s structure. The coating had a microhardness of 300 ± 21.5 HV0.2 when the cladding current was 80 A for the solid solution strengthening. The HEA coating had the highest corrosion potential of −0.253 V when the plasma current was 60 A, which was much higher than the grey cast iron’s corrosion potential of −0.708 V. Meanwhile, the coating had a much lower corrosion current density of 9.075 × 10−7 mA/cm2 than the grey cast iron’s 2.4825 × 10−6 mA/cm2, which reflected that the CoCrFeNiMn HEA coating had much better corrosion resistance and lower corrosion rate than the grey cast iron for single FCC solid solution phase and a relatively higher concentration of Cr in the grain boundaries than in the grains and this could lead to corrosion protection effects.